AI for people and business : a framework for better human experiences and business success - Castrounis, Alex (O'Reilly Media, Inc., 2019)
What are the risks, considerations, trade-offs, and constraints for pursuing an artificial intelligence project for your business? This practical book describes the value of AI and shows executives, data scientists, and software engineers how to align AI with company goals. Author Alex Castrounis introduces a framework that executives and practitioners can use to gain the most value with AI, while mitigating risk and ensuring the best chance of success. This framework will help you determine why AI is a fit for your business and provides a guide for all the AI project processes that follow-including data ingestion, model selection and training, model tuning, and results delivered. Learn why and how to use AI for achieving business goals Get a big-picture view of the potential business value of AI Align AI to your business goals using a framework to help you identify opportunities.